Flood-associated disease outbreaks and transmission in Southeast Asia - Tan, Boonfei; De Vera, Patrick; Abrazaldo, Josephine; Ng, Charmaine (Frontiers in Microbiology, 2025)
Southeast Asia (SEA) is among the world’s most flood-prone regions, where climate change is intensifying rainfall and extreme weather events. Floods disrupt communities and pose risks of infectious disease by bridging human, animal, and environmental reservoirs of pathogens. These events add strain to countries with vulnerable healthcare systems and critical infrastructure. Regional platforms such as the ASEAN Coordinating Centre for Humanitarian Assistance (AHA) and the ASEAN Biodiaspora Virtual Centre provide valuable weekly updates on emerging infectious diseases that could support disaster preparedness and response by incorporating supporting epidemiological and environmental data on waterborne outbreaks. Evidence synthesized in this review shows how floods reshape pathogen persistence, transmission pathways, host–environment interactions, and antimicrobial resistance (AMR), within the SEA context. By complementing existing regional monitoring endeavors, a One Health perspective emerges as a useful lens to capture the interconnected nature of risks across human, animal, and environmental domains. Advances in wastewater and environment-based surveillance, coupled with multi-omics approaches and machine learning, create new opportunities to detect diverse pathogens, integrate complex datasets, and forecast risks with more precision. This review addresses the importance of considering pathogen transmission before, during and after flood events, framing infectious disease risks within broader ecological and socio-economic contexts. By adopting this holistic perspective within the one-health paradigm, SEA countries could strengthen preparedness and resilience strategies before disasters occur.